IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH MELALUI STRATEGI ENTREPRENEURSHIP - Priti Elitawati; Mohammad Syahidul Haq (Jurnal Administrasi, Kebijakan, dan Kepemimpinan Pendidikan (JAK2P), 2020)
The aim of this study is to describe and to analyze the implementation of School-Based Management through entrepreneurship strategy. Besides to describe the implementation of entrepreneurship activities, this study is also to analyze the supporting factors and inhibiting factors of the implementation of entrepreneurship programs in SMP Muhammadiyah Surabaya. This study used qualitative approach with descriptive method. The data collection techniques used interview, observation, and documentation study. The data were analyzed by using data condensation, data presentation, and data verification. Checking the validity of the data were done by credibility, transferability, dependability, and confirmability. The results of this study are: (1) The implementation of SBM in SMP Muhammadiyah Surabaya was done through the urban farming entrepreneurship strategy by using classroom learning methods and outside classroom learning. The learning process was done by multilevel concept starting from seventh grader students to ninth grader students. Besides urban farming entrepreneurship, there is also IPM entrepreneurship. (2) The supporting factors of SBM implementation through entrepreneurship strategy are cooperation conducted by the school and outside school and the activeness between IPM members and other students in carrying out entrepreneurship activities in the school. (3) The inhibiting factors of SBM implementation through entrepreneurship strategy Surabaya are that there has not been a meeting with students’ parents to discuss the implementation of entrepreneurship programs and there is no substitute teacher to teach entrepreneurship subject in order to make the learning is more effective.